The national themes in the Poetry of Abd al-Sahib al-Barqʿawi (Journal of Imam Al-Kadhim College, 2026)
This study examines the national themes in the poetry of Sheikh Abdul Sahib Al-Barqa‘awi (1931–1995), one of Iraq’s distinguished poets, a native of the holy city of Najaf, and a graduate of its religious seminary. The poet addressed the theme of the homeland in a large number of his poems, driven by a strong sense of national feeling and pan-Arab affiliation with the sons of Arabism.The research is divided into four sections. The first discusses the concept of the homeland in Al-Barqa‘awi’s poetry. The second examines his engagement with national issues. The third addresses the poet’s interaction with the causes of the Arab nation, while the final section explores his inspiration from religious and historical symbols and their employment in national causes. These sections are preceded by an introduction that presents the poet and outlines the national themes, and followed by a conclusion summarizing the main findings of the study.
Keywords: National themes; Abdul Sahib Al-Barqawi; Commitment; National poetry